3ln(2)-2ln(3)=0

Simple and best practice solution for 3ln(2)-2ln(3)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3ln(2)-2ln(3)=0 equation:


Simplifying
3ln(2) + -2ln(3) = 0

Reorder the terms for easier multiplication:
3 * 2ln + -2ln(3) = 0

Multiply 3 * 2
6ln + -2ln(3) = 0

Reorder the terms for easier multiplication:
6ln + -2 * 3ln = 0

Multiply -2 * 3
6ln + -6ln = 0

Combine like terms: 6ln + -6ln = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 48=-4(-3x-6) | | -14=a+24 | | x=3r-12 | | 2(2n+3)=10 | | (-1)x=-10 | | 5x^2+24x+27=0 | | m-16=8 | | 3+3r-4r=-1 | | 3(10-2n)=0 | | 8+y=-7 | | 1.4f+1.1=8.3f | | 26y=32 | | 1.4f+1.1=8.3f | | 2x=-(-8) | | r^2+2r+2=0 | | 4.8=-16+1.6z | | 5(2n+1)=25 | | 0.75w+4=-3(0.75w+2)+8 | | 6x-2(x-2)=9x+4 | | (-2)x=-5 | | 6a^2-13a+5=0 | | -3.8d=8.74-1.9d | | x-(-6)=-80 | | 10(n-2)=100 | | -22=r+3+4r | | [4u-2]=10 | | -17=-5a+7-4 | | 3(9-7)=2(10+9) | | 55-4x=8x+22 | | 5g+4(-5+3g)=1-9 | | x-41=-58 | | 6x-5=-8X-2 |

Equations solver categories